Pengaruh Pengembangan Diri Terhadap Motivasi Belajar Bahasa Arab - Syafitri, Nila Sari; Kamal Yusuf (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2025)
Ibn Taimiyah emphasized that Arabic belongs to the integral elements of Islam, and learning it is considered a necessity, because understanding the Qur'an and As-Sunnah cannot be achieved without Arabic. Thus, motivation to learn Arabic becomes an important aspect in learners' mastery of the language. Self-development is acknowledged as a factor that influences motivation to learn. This study aims to identify the correlations between self-development and students' learning motivation and the extent to which self-development affects their motivation to learn. The research method used in this study is quantitative with a descriptive correlational approach. The sampling consisted of seventh-grade students of MTs Sirojul Haromain, Gresik. The research findings showed a positive & significant relationship between self-development and students' motivation to learn, with a correlation value of r = 0.687 and significance of p = 0.001 (p < 0.01). The Cronbach's Alpha value of 0.890 indicates that the instrument in this study has excellent internal consistency.